Measles Distribution Map By Measles Immunization In Banyuwangi 2014 – 2016 Using Health Mapper Application - Agustina, Nanda; Puspikawati, Septa Indra; Firdaus, Halimah (Tadulako University, 2020)
Measles disease is one of the infectious diseases caused by the Paramyxovirus Virus. Indonesia is one of the countries that has the largest number of measles cases in the world according to WHO (World Health Organization). Banyuwangi Regency is already able to give measles immunization more than 95% in accordance with the standards stipulated by the Ministry of Health of the Republic of Indonesia. However, the occurrence of measles cases is also still not reduced annually. This scientific article can help to see the tendency of measles occurrences seen from the scope of Immunisation in the local area. This type of research is a study by using secondary data health Profiles Banyuwangi District Health Office in 2014.205, and 2016. With the kind of observational research and design construct the research used is cross sectional. Descriptive data analysis using the Health Mapper version 4.3.0.0 with version 4.03. Results of the analysis obtained that the coverage of measles immunization in Banyuwangi district fluctuated in the year 2014 there is a coverage of the Banyuwangi Regency immunization of 102.4% d, in 2015 as much as 101.8% and in the year 2016 IE as much as 106.3. This is inversely proportional to the incidence of measles in Banyuwangi regency which increased in 2015 as many as 2 cases in the year 2014 the number of cases is still 0 and has a fixed value in the year 2016 IE as many as 2 cases are still the same as the year 2015.